Methodology for the design and comparison of optimal production configurations of first and first and second generation ethanol with power. (15th December 2016) - Bechara, Rami; Gomez, Adrien; Saint-Antonin, Valérie; Schweitzer, Jean-Marc; Maréchal, François
Graphical abstract: Highlights: 1st generation (1G) ethanol and power vs. 1G and 2G ethanol and power processes. Application of simulation-optimization-selection method for optimal process design. Optimization results have efficiencies, costs and utilities better than literature. 2G ethanol competitive only for 2G ethanol prices 2–4 times higher than normal. Similar design for two processes saves evaporation, utilities, hydrolysis and drying. Abstract: This article applies a systematic methodology to the optimization and comparison of two sugarcane conversion processes of great potential: the production of first generation ethanol and electricity in an integrated distillery and cogeneration plant (1G+COGEN), and the production of first and second generation ethanol and electricity in an integrated distillery, hydrolysis and cogeneration plant (1G+2G+COGEN). The employed method consisted of rigorous process simulation, heat integration, thermo-economic evaluation, bi-objective, exergy efficiency vs. capital cost, optimization and selection via profitability maximization. The exergy efficiency of optimal 1G+COGEN and 1G+2G+COGEN configurations ranged from 37.5% to 41.7% and from 41.8% and 44.42% respectively. Fixed capital increased with exergy efficiency from USD 155 million to USD 209 million and from USD 252 million to USD 393 million respectively. Ethanol production rate averaged at 81.4 L/ton cane (TC) for 1G+COGEN configurations whereas it increased with exergy efficiency to 106 L/TC for 1G+2G+COGEN schemes. Electricity production increased for the first from 122 to 188 kW h/TC and decreased for the second from 180 kW h/TC to 92 kW h/TC. 1G+COGEN schemes presented higher NPV values with a minimum difference of 45 million than 1G+2G+COGEN schemes, with the maximum at an exergy efficiency of 40.65%. Equal profitability was obtained when second generation ethanol selling prices were set at values two to four times greater than the standard, with the most profitable 1G+2G+COGEN configuration having the greater efficiency at 44.4%. A comparison of the two schemes displayed key similarities relating to vapor bleeding, heat integration, backward integrated distillation, high boiler pressure and superheating temperature, but also witnessed discrepancies in the evaporators and steam turbines. This work provides a stepping stone in the design of sustainable sugarcane conversion processes, and serves as an example for the efficiency of such methods for the conception of sustainable energy systems.